Prevalência de alterações locais e sistêmicas em indivíduos com disfunção temporomandibular - Uekama, Ira Cristina; Palinkas, Marcelo; Regalo, Simone Cecilio Hallak; Silva, Silvio Rocha Corrêa da [UNESP]; Siéssere, Selma; Semprini, Marisa; Bataglion, César (My University, 2012)
Temporomandibular disorder describes a variety of conditions including joint and muscle in the stomatognathic system, characterized by pain, TMJ sounds, functions irregular jaw and represent the leading cause of nondental pain in the orofacial region. The objective of this research was to evaluate the prevalence of ophthalmological, otological and cognitive-behavioral changes, parafunctional habits in individuals with temporomandibular disorders (TMD). A total of 117 medical records of female and male individuals, aged 18 to 60 years, from the Occlusion, Temporomandibular Dysfunction and Orofacial Pain of the Ribeirão Preto School of Dentistry – USP, between 2010 and 2011. The anamnesis index proposed by Helkimo was used to classify the individuals according to TMD severity degree and to divide them into two groups: AiI (mild to moderate) with 69 individuals and AiII (severe) with 48 individuals. The groups were then subdivided with respect to gender (72.64% female and 27.36% male) and age. There was predominance in the 18-40 year age group (60.68%) when compared to the 41-60 year age group (39.32%). Data were collected through an interview with questions about the presence of parafunctional habits, otological, ophthalmological and behavioral changes. Data were subjected to the statistical analysis using the Kruskal-Wallis test. The prevalence of each change was also evaluated. The results showed statistically significant for all groups according to gender, age and degree of severity. Individuals with temporomandibular disorders exhibited high prevalence of systemic and local dysfunctions.

Disfunção temporomandibular descreve uma variedade de condições que incluem alterações articulares, musculares no sistema estomatognático, caracterizados por dor, ruídos na ATM, funções irregulares de mandíbula e representam a principal causa de dor não dental na região orofacial. O objetivo desta pesquisa foi avaliar a prevalência de alterações oftalmológicas, otológicas, hábitos parafuncionais, alterações cognitiva-comportamentais em indivíduos com disfunção temporomandibular (DTM). Foram analisados 117 prontuários de indivíduos dos gêneros masculino e feminino na faixa etária de 18 a 60 anos do serviço de Oclusão, Disfunção Temporomandibular e Dor Orofacial da Faculdade de Odontologia de Ribeirão Preto – USP entre os anos de 2010 e 2011. O índice de anamnese proposto por Helkimo foi utilizado para classificar os indivíduos de acordo com o grau de severidade da DTM e dividi-los em dois grupos: AiI (leves a moderados) com 69 indivíduos e AiII (severos) com 48 indivíduos. Os grupos foram subdivididos com relação ao gênero (72.64% mulheres e 27.36% homens) e faixa etária. Houve predominância na faixa etária 18-40 anos (60,68%) quando comparado com o grupo etário 41-60 anos (39,32%). Os dados foram coletados por meio de entrevista, onde os indivíduos foram questionados quanto à presença de hábitos parafuncionais, alterações otológicas, oftalmológicas e comportamentais. Os dados foram submetidos à análise estatística, utilizando o teste de Kruskal-Wallis. A prevalência de cada alteração também foi avaliada. Os resultados mostraram estatisticamente significante para todos os grupos, de acordo com gênero, idade e grau de severidade. Indivíduos com disfunções temporomandibulares apresentaram alta prevalência de disfunções sistêmicas e locais.
Prevalence of systemic and local changes in individuals with temporomandibular disorder
Keywords: Temporomandibular disorder; Orofacial pain; Prevalence; Disfunção temporomandibular; Dor orofacial; Prevalência